INFLUENCE SELF-COMPASSION TO LONELINESS FOR TEENAGERS WHO ARE VICTIMS OF BULLYING - Irene Cristin Pasaribu; Ade Rahmawati Siregar (RADJA PUBLIKA, 2026)
Bullying can cause impact psychological Serious, like loneliness on victim . Self- compassion can help reduce impact negative with accept suffering experienced. Study This aim know influence self-compassion to loneliness in adolescent victims of bullying . The study used a quantitative method with convenience sampling. on 398 teenager victim bullying in Indonesia. Data collected through The University of California, Los Angeles Loneliness Scale Version 3 (UCLA LS), Self-compassion Scale (SCS), And The Revised Olweus Bully/Victim Questionnaire (OBVQ). Analysis data use regression linear simple show Self-compassion has a significant negative effect on loneliness with a contribution of 8.8% (R²=0.088), temporary 91.2% influenced factor other. Results This can help school, person old, And maker policy understand condition teenager in Indonesia.